2014
DOI: 10.1021/ac503860d
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed and Amplified Electronic Sensor for the Detection of MicroRNAs from Cancer Cells

Abstract: The detection of microRNA expression profiles plays an important role in early diagnosis of different cancers. On the basis of the employment of redox labels with distinct potential positions and duplex specific nuclease (DSN)-assisted target recycling signal amplifications, we have developed a multiplexed and convenient electronic sensor for highly sensitive detection of microRNA (miRNA)-141 and miRNA-21. The sensor is constructed by self-assembly of thiol-modified, redox species-labeled hairpin probes on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…Therefore, there are urgent demands for constructing sensitive and selective sensing methods for miRNA detection. Recently, various strategies, such as electrochemistry (Yang et al, 2014), fluorescence (Degliangeli et al, 2014;Wu et al, 2014), chemiluminescence (Deng et al, 2013a(Deng et al, , 2013b, colorimetry (Zhou et al, 2015;Shen et al, 2013), backscattering interferometry (Adams et al, 2013), and mass spectrometry (Popova and Williamson, 2014), etc. have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are urgent demands for constructing sensitive and selective sensing methods for miRNA detection. Recently, various strategies, such as electrochemistry (Yang et al, 2014), fluorescence (Degliangeli et al, 2014;Wu et al, 2014), chemiluminescence (Deng et al, 2013a(Deng et al, , 2013b, colorimetry (Zhou et al, 2015;Shen et al, 2013), backscattering interferometry (Adams et al, 2013), and mass spectrometry (Popova and Williamson, 2014), etc. have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, this enzyme can clearly discriminate among mismatched duplexes, even a one-base mismatch. 11,12 Therefore, analytic specificity has been significantly improved with DSN-mediated analytical strategies, including colorimetric assays, [13][14][15] electrochemistry, [16][17][18][19][20][21][22][23][24] fluorescence,…”
Section: Introductionmentioning
confidence: 99%
“…17,21,22,[53][54][55][56] Furthermore, we demonstrated that the DSN-assisted colorimetric assay can be converted into an electrochemical analysis with improved sensitivity and specificity. Specifically, the DNA probe immobilized on the electrode surface and that labeled with ferrocene (Fc) (denoted "Fc-DNA-Fc") in the solution triggered the in situ assembly of positively charged AuNPs through electrostatic interaction.…”
mentioning
confidence: 99%
“…Increasing studies have shown that altered expression profiles of miRNAs are closely associated with a number of diseases, especially human cancers (Lu et al, 2005;Yanaihara et al, 2006;de Planell-Saguer and Rodicio, 2011). Because of their significant biological roles, miRNAs can therefore serve as potential biomarkers for the diagnosis of different cancers (Hammond, 2006;Cissell et al, 2007;Cissell and Deo, 2009;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%